PENGARUH PESAN KAMPANYE ANTI MEROKOK TERHADAP SIKAP MASYARAKAT - Christina Meiliana Sitindaon (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2021)
Abstract This research was conducted in order to analyze the impact given related to information on smoking bans delivered through social media which is expected to be able to give effect to the public regarding smoking. And this research was conducted with a quantitative approach using survey methods conducted by distributing questionnaires as data collection. The number of respondents in this study were 97 people who were sampled using the Non-Probability Sampling Technique. Non-Probability sampling technique used in this study is purposive sampling where respondents in this study have criteria that will be used as samples, namely people who have seen or know information about smoking bans. Data analysis in this study used Univariate and Regression Test, after being analyzed the data was processed using SPSS. And the results of this study that Expression of Anti-Smoke Messages and Reception of Anti-Smoke Messages have a significant effect on Perceived Peer Smoking Norms, while Expression of Anti-Smoke Messages and Reception of Anti-Smoke Messages have a significant effect on Smoking Intentions. So in conclusion Information about smoking bans delivered through social media can affect a person's way of smoking because people who receive information submitted in the form of words or submitted by posting pictures on social media can make someone interested in reading and commenting on smoking-related information.Keywords: (Campaign PR, Anti Smoke Messages, Social Media, Intentions, Attitude)